A Catholic New Woman Artist: A Contradiction in Terms? Sex, Music and Religion in George Moore’s Evelyn Innes and Sister Teresa - Jędrzejewski, Jan (The Woman Artist: Essays in memory of Dorota Filipczak, 2024)
The paper offers an overview of George Moore’s long-neglected novels Evelyn Innes (1898) and its sequel Sister Teresa (1901), focusing on the presentation of their eponymous protagonist as a woman, an artist, and a committed if independent-minded Roman Catholic. The two novels constitute an extended study of the relationship between artistic inspiration, sensuality, and religious experience: Evelyn Innes, an opera singer who ultimately chooses to join a religious order and become a nun, tries to reconcile in her life the conflicting demands of her vocation as an artist, her passionate nature, her personal and religious loyalties, and the expectations of Victorian society. Focusing on the novels’ interwoven musical and religious imagery, the chapter traces the presentation of Evelyn’s growth as a character, arguing, in the context of the development of late Victorian fiction, that she emerges as a rare example of a Catholic New Woman artist; at the same time, the novels shed some light on George Moore’s perception of the interface of the issues of aesthetics, gender, and religion in the context of turn-of-the-century British and Irish social, literary, and cultural life.